2001
DOI: 10.1002/1097-0142(20010615)91:12<2329::aid-cncr1265>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for unresectable ovarian carcinoma

Abstract: Wood is a hierarchical composite, consisting at its lowest hierarchy level of crystalline cellulose elementary fibrils with diameters of 2–4 nm embedded in a matrix of hemicelluloses and lignin. At the micrometer scale, it has a cellular architecture resembling a honeycomb structure. The transformation of the hierarchical wood structure into a silica replica has been reported recently. Its formation process and structural details are studied in this contribution. First, a silica/biopolymer composite is prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(26 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Multiple studies have shown that neoadjuvant chemotherapy can improve the surgical condition for AOC patients that fail to receive a surgical operation, with enhancement of surgical optimality, reduction of postoperative recurrence and improvement of prognosis etc. [2,3] Neoadjuvant chemotherapy, combined with cytoreduction, has become a selectable regimen for AOC treatment. In this article we have reviewed advances in the preoperative evaluation of AOC cytoreduction.…”
supporting
confidence: 89%
“…Multiple studies have shown that neoadjuvant chemotherapy can improve the surgical condition for AOC patients that fail to receive a surgical operation, with enhancement of surgical optimality, reduction of postoperative recurrence and improvement of prognosis etc. [2,3] Neoadjuvant chemotherapy, combined with cytoreduction, has become a selectable regimen for AOC treatment. In this article we have reviewed advances in the preoperative evaluation of AOC cytoreduction.…”
supporting
confidence: 89%
“…Multiple studies suggested that patients of advanced ovarian cancer treated with NAC improved performance status, decreased the extent and morbidity of surgery, and increased the opportunity of optimal debulking surgery [2,[4][5][6][7][8][10][11][12]. Therefore, it is natural to consider NAC followed by IDS to be an alternative to conventional PDS in treating advanced ovarian cancer and expect that the NAC group would have better survival than PDS group.…”
Section: Discussionmentioning
confidence: 99%
“…The 4% response rate noted in this study was significantly lower than the previously reported response rates of 60% to 80% for neoadjuvant chemotherapy in patients with high-grade serous ovarian carcinoma [33,34]. These fi ndings suggest that low-grade serous carcinomas of the ovary and peritoneum are not as responsive as high-grade serous carcinomas are to conventional chemotherapy with platinum and taxane agents.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%